The efects of couplant and the relation between probe angle and defect variation in ultrasonic inspection / Abdul Rahman Md Noor - Md Noor, Abdul Rahman (2010)
Couplant and defect variation plays a main role to the inspection process. In this study, the effects of couplant to the inspection have been investigated and the relation between the probe angles and defect variations has been studied. Using the pulse echo technique, inspection has been done to the high measurement block with angle probes and the type of couplant is varies. This height measurement block is a standard block which has several side drill holes in many variation of angle. These side drill holes will act as the defects in the sample. The best probe and couplant and is the probe and couplant which gives the highest maximum reflection with low gain consumed. As a result, the best couplant is the Krautkramer Gel couplant and the relation of probe angle and defect variation is concluded. When the best probe is 45°, the range of variation of defect is about from 40° to 50°. When the best probe is 60°, the range of variation of defect is about from 25° to 35°. When the best probe is 70°, the range of variation of defect is about from 15° to 25°.